The new encyclopedia británica in 30 volumes, macropedia VOL.19 3. William Benton - Benton, William (Estados Unidos de América: Encyclopedia Británica, Inc, 1977)
The land, the people, the economy, administration and social conditions, cultural life and institutions, the outlook, application of vacuum, equipment for achieving, maintaining, and measuring a vacuum, western art music, variation in non-westers music, environments and varve and formation, evaluation of techniques used to determine annual accumulations, origin of cultivated vegetables, vegetable classification, vegetable by-products, types of production.
Ilustración, mapa, tabla
Col. Enc
Keywords: 1. ENCICLOPEDIA 2. ENCYCLOPEDIA BRITANNICA-MACROPEDIA VOL. 19 3. REFERENCE